Factors Influencing Syariah Stock Returns in Jakarta Islamic Index (JII) 2014-2023 - Siswanto, Dodi (Jurnal Dialektika: Jurnal Ilmu Sosial, 2025)
This study aims to analyze the factors that influence the return of sharia stocks on the Jakarta Islamic Index (JII). The background of this study is based on the conditions of uncertainty in the return of sharia stocks where significant fluctuations are seen. This study uses a quantitative approach with an explanatory survey method. The population in this study were companies included in the Jakarta Islamic Index (JII) for the period 2014-2023, the sample was selected using a purposive sampling technique with a total of 14 companies. Testing was carried out using a descriptive statistical approach and panel data regression, t-test, F-test. The results of the study showed that simultaneously stock risk, stock valuation, exchange rates and inflation affected stock returns. Partially, stock risk, stock valuation, and exchange rates had a positive effect on stock returns, while inflation had a negative effect on stock returns.